Mixed lipopeptide-based mucosal vaccine elicits a long-term bone marrow memory response that is potentially cross-reactive against a broad-spectrum of coronaviruses in mice - Patel, Raj S.; Agrawal, Babita (Frontiers in Immunology, 2025)
IntroductionSARS-CoV-2 is continuing to prevail as an endemic virus, and therefore, we need a next-generation vaccine that prevents SARS-CoV-2 infections, broadly protects against multiple CoVs, and induces long-term local and systemic immunity. To address that need, we have designed a mixed lipopeptide-based pan-coronavirus (LPMix) vaccine based on T and B cell epitopes derived from highly conserved and functional regions of the SARS-CoV-2 spike (S), nucleocapsid (N), and membrane (M) proteins.MethodsMale C57BL/6 mice (n=5 per group) were immunized intranasally twice, 14 days apart, with the LPMix vaccine candidates, which consisted of seven lipopeptides (LP1–LP7), with or without HKCC (heat-killed Caulobacter crescentus), a novel mucosal adjuvant. At 2.5 weeks, 2 months, and 7 months post-immunization, lung, spleen, bone marrow, and bronchoalveolar lavage (BAL) samples were collected for immunological analyses. Additionally, blood samples were collected monthly to monitor antibody titers.ResultsWe demonstrate that intranasal immunizations of mice with LPMix induced a long-lasting systemic IgM/IgG, and mucosal IgA response against a broad-spectrum of CoVs, showing clinically significant levels of neutralizing antibody titers. Splenocytes and bone marrow cells, derived from LPMix immunized mice, demonstrated a robust proliferation response against vaccine antigens (P1-7), which were maintained up to 2 months and 7 months, after LPMix immunizations, respectively. Moreover, antigen-specific B cells and memory CD4+/CD8+ T cells were long-lived and maintained up to 7 months after LPMix immunizations, in the lungs, spleen and bone marrow. The addition of HKCC (heat-killed Caulobacter crescentus), a novel mucosal adjuvant, promoted the longevity of memory CD4+/CD8+ T cell and B cell responses.DiscussionOverall, our study demonstrates that a mucosal lipopeptide-based vaccine targeting conserved SARS-CoV-2 epitopes elicits durable, long-lasting immune responses against a broad range of coronaviruses.